Balloon aortic valvuloplasty in high risk aortic stenosis patients with left ventricular ejection fractions <20%. Issue 5 (8th August 2014) - Pedersen, Wes R.; Goldenberg, Irvin F.; Pedersen, Christopher W.; Lesser, Andrew; Harris, Kevin M.; Lesser, John R.; Garberich, Ross F.; Schwartz, Jonathan G.; Shank, Emily; Schwartz, Robert S.
<x xml:space="preserve">Abstract</x> Objectives To determine outcomes following balloon aortic valvuloplasty (BAV) in aortic stenosis (AS) patients with a left ventricular ejection fraction (LVEF) <20%. Background Severe AS patients with a LVEF <20% are excluded from United States (U.S.) transcatheter aortic valve replacement (TAVR) trials and often surgical aortic valve replacement (AVR). The role for BAV to enhance LVEF is unclear. Methods Our BAV database of 270 consecutive patients extending from 2005 through 2010 was queried for a preoperative LVEF <20%. Demographics, echocardiograms, procedural technique, and outcomes were analyzed. Pre‐ and postoperative echocardiograms were used to determine improvement in aortic valve area (AVA) and LVEF. Results Sixteen patients were identified with a median age of 82 years. The composite Society of Thoracic Surgeons' (STS) mortality risk was 16.4%. The median preoperative AVA and LVEF were 0.60 cm2 and 16%, respectively, and postoperative AVA and LVEF were 0.77 cm2 and LVEF 19%, respectively. About 15 of the 16 patients had postoperative echocardiograms available for comparison. And 7 of these 15 (47%) demonstrated improvement in LVEF to ≥20% (median LVEF 25%). The absence of coronary disease and improvement in AVA of ≥0.2 cm2 was associated with postoperative LVEF of ≥20%. Procedural mortality was 0%. The 30‐day, 6‐month, and 1‐year survival was 69%, 56%, and 29%. STS's mortality risk score ≥15% was associated with short‐term mortality. Conclusion With appropriate technique, BAV can be reasonably safe in patients with LVEF <20%. Roughly half of these patients demonstrated improvement in LVEF to ≥20%. © 2013 Wiley Periodicals, Inc.